A Social Network Analysis of Friendship and Spiritual Support in a Religious Congregation. Issue 1 (22nd July 2019) - Todd, Nathan R.; Blevins, Emily J.; Yi, Jacqueline
Abstract: Religious congregations are social settings where people gather together in community to pursue the sacred (Pargament, 2008). Such settings are important to understand as they provide a context for individuals to develop relationships, share ideas and resources, and connect individuals to larger society (Todd, 2017a). Yet, research to date has not deeply examined the inherently relational nature of religious congregations. Thus, in this study, we used social settings theory (Seidman, 2012; Tseng & Seidman, 2007) to develop and test hypotheses about relationships within one Christian religious congregation. In particular, we used social network analysis to test hypotheses about relational activity, popularity, and homophily for friendship and spiritual support types of relational links. Our findings demonstrate how relational patterns may be linked to participation in congregational activities, occupying a leadership role, a sense of community and spiritual satisfaction, stratification, socialization, and spiritual support. Overall, this advances theory and research on the relational aspects of religious congregations, and more broadly to the literature on social settings. Limitations, directions for future research, and implications for theory and religious congregations also are discussed. Highlights: Used social settings theory to frame hypotheses about relationships in a Christian congregation. Examined friendship and spiritual support as two types of relational links. Tested hypotheses about relationships in a congregation using social network analysis. Used ERGM models to test hypotheses about relational activity, popularity, and homophily. Showed utility of using network methods to test hypotheses related to social settings theory.